2013
DOI: 10.1007/978-1-4614-8090-7_7
|View full text |Cite
|
Sign up to set email alerts
|

ROUNDABOUT Receptors

Abstract: Roundabout receptors (Robo) and their Slit ligands were discovered in the 1990s and found to be key players in axon guidance. Slit was initially described as an extracellular matrix protein that was expressed by midline glia in Drosophila . A few years later, it was shown that, in vertebrates and invertebrates, Slits acted as chemorepellents for axons crossing the midline. Robo proteins were originally discovered in Drosophila in a mutant screen for genes involved in the regulation of midline crossing. This li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 213 publications
(248 reference statements)
0
12
0
Order By: Relevance
“…When one or the other molecule was not present, the axons could cross. However, subsequent studies have revealed a more complex story for these genes, including involvement in cell proliferation and migration of neuronal and non-neuronal cells, and axon pathfinding and dendritic branching of neurons (Brose and Tessier-Lavigne, 2000;Lopez-Bendito et al, 2007;Ypsilanti et al, 2010;Kolodkin and Tessier-Lavigne, 2011;Blockus and Ch edotal, 2014;Ypsilanti and Chedotal, 2014). Furthermore, the different SLITs can bind to the different ROBO receptors in various combinations, including among different splice variants, leading to either repulsive or attractive interactions between neurons (Blockus and Ch edotal, 2014;Ypsilanti and Chedotal, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When one or the other molecule was not present, the axons could cross. However, subsequent studies have revealed a more complex story for these genes, including involvement in cell proliferation and migration of neuronal and non-neuronal cells, and axon pathfinding and dendritic branching of neurons (Brose and Tessier-Lavigne, 2000;Lopez-Bendito et al, 2007;Ypsilanti et al, 2010;Kolodkin and Tessier-Lavigne, 2011;Blockus and Ch edotal, 2014;Ypsilanti and Chedotal, 2014). Furthermore, the different SLITs can bind to the different ROBO receptors in various combinations, including among different splice variants, leading to either repulsive or attractive interactions between neurons (Blockus and Ch edotal, 2014;Ypsilanti and Chedotal, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…striking downregulation of SLIT1 in the RA analogs of all vocal learners. This overall hypothesis would be viable if, as opposed to common belief (Blockus and Ch edotal, 2014;Ypsilanti and Chedotal, 2014), SLIT1 protein is released from descending axons from the arcopallium neurons and ROBO1 protein is on the dendrites or cell bodies on brainstem motor neurons (Fig. 9).…”
Section: Discussionmentioning
confidence: 99%
“…Robo2 was first discovered as one of the four mammalian homologs to the Drosophila Roundabout gene ( Robo ), which was named because of the unique axonal recrossing pattern generated at the CNS midline (Seeger et al, 1993; Kidd et al, 1998; Brose et al, 1999; Simpson et al, 2000). Further studies found that Robo family members perform additional axon guidance functions to regulate brain wiring broadly throughout the nervous system (Ypsilanti and Chedotal, 2014), including midbrain dopamine neurons (Dugan et al, 2011). Additional studies expanded the essential functions of Robo2 to include cell migration, synaptogenesis, synaptic plasticity, neuronal survival, and dendritic patterning during prenatal and early postnatal development (Shen and Cowan, 2010; Gibson et al, 2014; Koropouli and Kolodkin, 2014; Ypsilanti and Chedotal, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies found that Robo family members perform additional axon guidance functions to regulate brain wiring broadly throughout the nervous system (Ypsilanti and Chedotal, 2014), including midbrain dopamine neurons (Dugan et al, 2011). Additional studies expanded the essential functions of Robo2 to include cell migration, synaptogenesis, synaptic plasticity, neuronal survival, and dendritic patterning during prenatal and early postnatal development (Shen and Cowan, 2010; Gibson et al, 2014; Koropouli and Kolodkin, 2014; Ypsilanti and Chedotal, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The Slit-Robo signaling pathway has roles in a number of developmental processes, primarily axon guidance, cell movement, and cell adhesion (Blockus and Chédotal, 2016;Chédotal, 2007;Wu et al, 2017;Ypsilanti and Chedotal, 2014;Ypsilanti et al, 2010). Slit ligand binding to Robo receptors can induce cell migration using repulsive or attractive cues in a context-dependent manner.…”
Section: Introductionmentioning
confidence: 99%